2021
DOI: 10.1161/circulationaha.120.051680
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation by Suv4-20h1 in Cardiopulmonary Progenitor Cells Is Required to Prevent Pulmonary Hypertension and Chronic Obstructive Pulmonary Disease

Abstract: Background: The etiology of life-threatening cardiopulmonary diseases such as Pulmonary Hypertension (PH) and Chronic Obstructive Pulmonary Disease (COPD) originates from a complex interplay of environmental factors and genetic predispositions, which is not fully understood. Likewise, little is known about developmental abnormalities or epigenetic dysregulations that might predispose for PH or COPD in adult individuals. Methods: To identify pathology-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…First, we isolated CPPs from E9.5 murine embryos, maintained CPPs stemness while expanding them with ABC medium, and confirmed that CPPs harbour the unique potential to differentiate into two lineages of cells, which is in line with the latest publication showing that Isl1+ CPPs give rise to SMC, EC, EpiC, and alveolar myofibroblasts. 19 Data from scRNA-seq demonstrated that CPPs we obtained were a population mainly composed of heterogenic stem cells expressing CPPs marker Isl1, and exhibited a hybrid fibroblastic and endothelial state, which is similar to another study that found that pituitary stem cells are in a hybrid epithelial and mesenchymal state. 38 Additional analysis is needed to demonstrate the membrane markers for our CPPs, and verification experiment should be performed.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…First, we isolated CPPs from E9.5 murine embryos, maintained CPPs stemness while expanding them with ABC medium, and confirmed that CPPs harbour the unique potential to differentiate into two lineages of cells, which is in line with the latest publication showing that Isl1+ CPPs give rise to SMC, EC, EpiC, and alveolar myofibroblasts. 19 Data from scRNA-seq demonstrated that CPPs we obtained were a population mainly composed of heterogenic stem cells expressing CPPs marker Isl1, and exhibited a hybrid fibroblastic and endothelial state, which is similar to another study that found that pituitary stem cells are in a hybrid epithelial and mesenchymal state. 38 Additional analysis is needed to demonstrate the membrane markers for our CPPs, and verification experiment should be performed.…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, there is no reported research on whether CPPs have the ability to repair the heart. Articles on CPPs are few and focus mainly on the regulation of heart or lung development 19 . The roles of CPPs in repairing damaged hearts need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human asthma samples were received from the BioMaterialBank Nord, Clinical and Experimental Pathology Medicine, Research Center Borstel. Human donor samples, human COPD samples and human cystic fibrosis samples were provided by the DZL Biobank were obtained during lung transplantation of human COPD and cystic fibrosis patients 36 . Donor lung material was obtained as a result of atypical resections undertaken to adjust the donor organ to the recipient’s thoracal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…However, a detailed time course of KMT5B expression in model systems is lacking. Loss of KMT5B results in altered development of both the brain and cardiopulmonary system ( 23 , 24 ). Evidence of KMT5B’s role in neurogenesis is available for many models [zebrafish ( 25 , 26 ), amphibian ( 27 ), rodent ( 28 ), and primate ( 29 ) model systems].…”
Section: Introductionmentioning
confidence: 99%